The Influence of Transformational Leadership on Employee Performance at the South Bulango District Office, Bone Bolango Regency - Mohamad Fadliyanto Yusuf; Yacob Noho Nani; Rusli Isa (Universitas Negeri Gorontalo, 2025)
This study aims to determine the effect of transformational leadership on employee performance at the Bulango Selatan District Office, Bone Bolango Regency. The research method used was descriptive quantitative, with a sample of 30 employees drawn from all employees at the Bulango Selatan District Office. Data were collected through questionnaires and analyzed using simple linear regression. The results showed that transformational leadership had a positive and significant effect on employee performance, with a correlation coefficient of 0.833 and a coefficient of determination (R²) of 0.694. This means that transformational leadership contributed 69.4% to employee performance improvement, while the remaining 30.6% was influenced by other factors. This finding confirms that the better the implementation of transformational leadership, the higher the employee performance at the Bulango Selatan District Office.